Local public services delivery mechanisms - Petkovšek, Veronika (Lex localis, 2021)
The paper presents a systematic literature review on local public services delivery mechanisms, in-house provisions, privatization and inter-municipal cooperation, for the period 2007 to 2018, with the aim of reviewing the development of the area under study, identifying which delivery mechanism dominates in a given period, and determining which economic research focus dominates in the area under study. Possible effects on economies of scale, cost reductions, efficiency, and other economic, political, institutional, and social factors in the provision of local public services are examined using a content analytical breakdown. The results show that most of the studies are country studies and, especially in recent years, empirical studies. The choice of local public services delivery mechanisms is mainly influenced by the size of local government, the efficiency of service provision, the available resources and the institutional framework. Politics and market competition also play a role in the decision-making process. Following the recent financial and economic crisis, inter-municipal cooperation is increasingly being researched as an efficient form of service provision.
Keywords: analiza; ekonomski vidik; javne storitve; lokalna samouprava; občine; privatizacija; sodelovanje